Resilience and quality of life in patients who underwent mechanical ventilation due to COVID-19, one year after discharge (2024)
Background: Patients with COVID-19 often experience severe long-term sequelae. This study aimed to assess resilience and Quality of Life (QoL) of patients who underwent mechanical ventilation due to COVID-19, one year after discharge. Methods: This cross-sectional study enrolled patients who received mechanical ventilation for severe COVID-19 and were assessed one-year post-discharge. Participants completed a structured questionnaire via telephone comprising the Connor-Davidson Resilience Scale (CD-RISC) and the Post-COVID-19 Functional Status scale (PCFS). To establish the association between QoL and resilience, Spearman correlations were calculated between the PCFS and the CD-RISC. Linear regression models were adjusted to evaluate which factors were associated with QoL, with the total score of PCFS as the dependent variable. Results: A total of 225 patients were included in the analysis. The CD-RISC had a median score of 83 (IQR 74–91). The PCFS results showed that 61.3% (n?=?138) of the patients were able to resume their daily activities without limitations. Among them, 37.3% (n?=?84) were classified as Grade 0 and 24% (n?=?54) as Grade 1. Mild and moderate functional limitations were found in 33.7% of the patients, with 24.8% (n?=?56) classified as Grade 2 and 8.8% (n?=?20) as Grade 3. Severe functional limitations (Grade 4) were observed in 4.8% (n?=?11) of the patients. High CD-RISC scores were associated with lower levels of PCFS score (p?<?0.001). Conclusions: In this cohort of critically ill patients who underwent mechanical ventilation due to COVID-19, 38% of patients experienced a significant decline in their QoL one year after hospital discharge. Finally, a high level of resilience was strongly associated with better QoL one year after discharge.